Rheum khorasanicum Decreases Migration and Induces Apoptosis in the MDA-MB-231 Breast Cancer Cell Line - Mehrabani, Mitra; Miri, Zahra; Juybari, Kobra Bahrampour; Najafi, Rezvan; Goki, Maryamossadat Mirtajaddini; Aminizadeh, Najmeh; Nematollahi, Mohammad Hadi; Vasei, Saeede; Mehrabani, Mehrnaz; Amirkhosravi, Arian (Letters in Drug Design & Discovery, 2024)
BackgroundRheum khorasanicum is a medicinal plant that belongs to the Polygonaceae family. This family is well-known for its anticancer activities.ObjectiveDue to the limited studies on the anticancer activity of R. khorasanicum, the present study aimed to evaluate the apoptotic effect of this medicinal plant on MDA-MB-231 cells as a model for an aggressive triple-negative breast cancer that has a lower treatment option.MethodsR. khorasanicum root was collected in April, 2021 from Neyshabur, Iran, and its hydroalcoholic extract was prepared using the maceration method. The High-Performance Thin-Layer Chromatography (HPTLC) assay was used to determine the main ingredients of the extract. The viability and apoptosis of the cells were evaluated by WST-1 and the annexin-V/PI dual staining assay, respectively. The scratch assay was used to assess the migratory potential of cancer cells, and the Western blotting test was employed for determining the expression of Bcl-2, Bax, cleaved caspase- 3, cleaved caspase-7, and procaspase-7 proteins involved in the apoptotic pathway.ResultsThe yield of extract from R. khorasanicum root was 56.8 ± 11.1%. The HPTLC analysis indicated that emodin, gallic acid, and epigallocatechin were pharmacologically active compounds isolated from the hydroalcoholic extract of R. khorasanicum root. The extract showed a significant toxic effect on MDA-MB-231 cells up to 60 µg/mL concentration. R. khorasanicum root extracts also inhibited the migratory potential of MDA-MB-231 at concentrations ≥ 60 μg/mL. The plant root extract at concentrations of 60 and 100 μg/mL significantly increased the Bax/Bcl-2 ratio cleaved caspase-3, cleaved caspase-7/ procaspase-7 protein levels compared to the nontreated cells.ConclusionOur findings demonstrated that the hydroalcoholic extract of R. khorasanicum efficiently triggered the apoptosis of MDA-MB-231 cells as a suitable model for aggressive triple-negative breast cancer, possibly by decreasing their migratory potential and stimulating the apoptotic signaling pathway.
Keywords: apoptosis